Penerapan Konsep Teori Sistem Model Betty Neuman Pada Asuhakan Keperawatan Pasien Stroke Diruang Rawat Inap Rumah Sakit Umum Pusat Fatmawati Jakarta - Feriadianto Feriadianto; Irna Nursanti (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Nursing theories are attempts to describe or explain nursing phenomena. Through nursing theory, it can be distinguished whether it includes scientific disciplines or other activities. Apart from being used to develop a model related to nursing concepts, nursing theory also has characteristics including: nursing theory identifies and explains special concepts related to real things in nursing. The main concepts identified in Betty Neuman's theoretical approach are the holistic approach, open system (including function, input and output, feedback, negent-copy, and stability), environment (including the created environment), client system (including five client variables, basic structure, line of resistance, normal line of defense, and flexible line of defense), health (fitness to disease), stressors, degree of reaction, prevention as intervention (three levels), and recovery.